IMPROVING STUDENT’S SPEAKING ACHIEVEMENT THROUGH GUIDED GRAMMAR IN POLITEKNIK KELAPA SAWIT BEKASI - Luluk SETYOWATI (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2019)
Speaking is an important skill in language learning, it is the key of active communication. As teaching speaking is important aspect in language learning process, this is a crucial part of second language learning and teaching. Despite this fact, for many years, teaching speaking in Indonesian context has been undervalued and English language teachers have continued to teach speaking as a repetition of drills or memorization of dialogues. However, today's education world requires that the goal of teaching speaking should improve students' communicative skills. Only in this way, the students can express themselves depend on the social context. In this study, the researcher attempts to conduct a research about the use of guided grammar and its impact in speaking achievement for students of oil palm plantation processing technology program of Politeknik Kelapa Sawit Bekasi. The activities of learning grammar provide an excellent opportunity for the learners to develop this skill. The result shows that at the beginning of guided grammar, students' speaking ability is still very limited. But when the speaking assignments in guided grammar went on for quite a long time, students were getting used to speak in grammatically correct way. Students felt that their speaking skills had improved and had become better than before.